Pilot operation and lifetime assessment for indoor light energy harvesting photovoltaics. (June 2020) - Hsiao, Po-Tsung; Hung, Wan-Tun; Chen, Yu-Cheng; Huang, Liang-Kun; Chang, Chih-Chou; Chen, Ching-Fu; Chen, Hao-Wei; Lu, Ming-De; Lin, Yu-Pin; Tung, Yung-Liang
Abstract: Photovoltaic cells for indoor light harvesting have recently attracted considerable attention for low power consumption electronic products due to the rapid growth of the Internet of Things. Dye-sensitized cells (DSC) show tremendous promise in delivering a low-cost, high-manufacturability, and excellent conversion efficiency for various artificial lights to combine with electronics achieving the energy autonomous system. Commercial DSC technology in terms of the reproducibility on cell efficiency and lifetime prediction was discussed to meet requirements of photovoltaic cell market for various applications. The DSC automated pilot line towards industrially relevant manufacturing volumes was described, providing an average efficiency of 13.8% at 1000 lux white LED light and an overall yield of 98.7%. Furthermore, an approach to obtain the database of degradation rate constant for various environmental stresses was proposed according to Arrhenius plots and can be used to predict DSC lifetime for a variety of situations. The lifetime was evaluated to 10.9 years for the indoor situation using the corresponding degradation rate constant. Graphical abstract: Image 1 Highlights: Automated production line of dye-sensitized cells was developed successfully. Automated production line achieves the high manufacture yield and reproducibility. A method to quantify lifetimes for various application conditions was proposed. DSC exhibits superior photovoltaic performance and lifetime in indoor applications. Commercial DSC is expected to fulfill the need of autonomous energy systems.